1995
DOI: 10.1088/0953-8984/7/4/006
|View full text |Cite
|
Sign up to set email alerts
|

Spin flop in goethite

Abstract: A spin-flop transition is observed when a field of 20 T is applied parallel to the h axis of a specimen of natural goethite at 4.2 K. The gwthite orders in a four-sublattice antiferromagnetic structure with the sublattice magnetizations inclined at i I 3 ' to b, and an iron moment of 3.90 pg. There is a small net ferromagnetic moment of 0.004 pg along b which has the eRect of more than doubling fhe threshold field for spin flop. The anisotropy field is deduced to be 0.1 1 T. cotresponding to a uniaxial anisotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
1
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 15 publications
10
68
1
1
Order By: Relevance
“…The DFT+U correction [166,167] was employed with a U = 4 eV for Fe and 0 eV for all other elements. Spin states were ordered according to the experimental observed magnetic ordering of goethite [168]. These selections have worked reasonably well in a previous study on goethite and goethite-water [73].…”
Section: Planewave Calculations Using α-Feooh (010)supporting
confidence: 83%
“…The DFT+U correction [166,167] was employed with a U = 4 eV for Fe and 0 eV for all other elements. Spin states were ordered according to the experimental observed magnetic ordering of goethite [168]. These selections have worked reasonably well in a previous study on goethite and goethite-water [73].…”
Section: Planewave Calculations Using α-Feooh (010)supporting
confidence: 83%
“…The χ AFM -value determined for our lepidocrocite sample, 5.34 × 10 −7 m 3 /kg, leads to T N = 392 K. For comparison, χ AFM in goethite is 3.96 × 10 −7 m 3 /kg (Coey et al, 1995), which corresponds to a theoretical value of T N = 532 K, close to the actual Néel temperature of about 400 K (e.g., Özdemir and Dunlop, 1996). In our lepidocrocite sample, the Néel temperature (ca.…”
Section: Isothermal Magnetizationmentioning
confidence: 70%
“…However, the model used to calculate the field dependence of the Mössbauer spectra and the spin-flop field was based on the assumption of uniaxial anisotropy and a collinear antiferromagnetic structure, although the magnetic structure of goethite is much more complicated. 43 Therefore the model seems to be too crude. Secondly, it has been shown that even a very small uncompensated magnetic moment in antiferromagnetic particles can result in a substantial increase of the spin-flop field, 43,44 and small antiferromagnetic particles will inevitably have an uncompensated moment.…”
Section: A Qualitative Interpretation Of the Resultsmentioning
confidence: 99%
“…43 Therefore the model seems to be too crude. Secondly, it has been shown that even a very small uncompensated magnetic moment in antiferromagnetic particles can result in a substantial increase of the spin-flop field, 43,44 and small antiferromagnetic particles will inevitably have an uncompensated moment. Furthermore, the anisotropy was estimated at low temperatures, but at higher temperatures, at which the model is applied, the anisotropy may be smaller.…”
Section: A Qualitative Interpretation Of the Resultsmentioning
confidence: 99%